2017
DOI: 10.1007/s10661-017-5766-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of lower resolutions of digital elevation model on rainfall-runoff modeling for ungauged catchments

Abstract: This paper investigates the integrated impacts of Digital Elevation Model and Land cover Resolutions on Simulated Runoff by SWAT Model. Though the paper seems to address an interesting issue of the integrated assessment of the influence of the DEM and LC resolution, that, to my knowledge formed by quick search in the recent papers, has not been addressed yet, however, I think that the paper quality is seriously flawed and would need a serious revision, before it can be considered for publication in HESS. Major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…from satellite imagery, such as ASTER and SRTM). In large areas (greater than 100 km 2 ), Ghumman et al (2017) found similar model efficiencies in the accuracy of rainfall-runoff models using both higher (5 or 10 m) and lower (30 and 90 m) DEM resolutions. However, in small areas (less than 1 km 2 ), the extra detail inherent in very high resolution (10 cm) terrestrial data is valuable when running surface models and analysing flood risk values (Sampson et al, 2012).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…from satellite imagery, such as ASTER and SRTM). In large areas (greater than 100 km 2 ), Ghumman et al (2017) found similar model efficiencies in the accuracy of rainfall-runoff models using both higher (5 or 10 m) and lower (30 and 90 m) DEM resolutions. However, in small areas (less than 1 km 2 ), the extra detail inherent in very high resolution (10 cm) terrestrial data is valuable when running surface models and analysing flood risk values (Sampson et al, 2012).…”
Section: Introductionmentioning
confidence: 55%
“…In agricultural catchments, DEM resolutions must be optimised in order to identify critical source areas of diffuse pollution and to capture any microtopographic features acting as topographic barriers or channels which divert runoff away from the hillslope scale flow direction (Thomas et al, 2017). In large areas (greater than 100 km 2 ), Ghumman et al (2017) found similar model efficiencies in the accuracy of rainfall-runoff models using both higher (5 or 10 m) and lower (30 and 90 m) DEM resolutions. LiDAR at 1 m) to a lower resolution reduces model accuracy much less than the use of low-resolution DEM (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate streamflow simulation is imperative to the sustainability of water resources. It is exceptionally challenging to implicate the procedure in these simulations due to its nonlinear and multidimensional dynamics [1]. Varied modeling techniques have been utilized to predict the streamflow, such as physically based distributed models [1][2][3], stochastic models [4], lumped conceptual models [5], and black-box models [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This type of data is not available in most of the arid environmental regions. However, advancements in satellite imaging and geographical information system (GIS) tools have introduced geomorphological parameters that can be used to estimate the runoff from catchments with scarce data [21][22][23].…”
Section: Hec-hms and Gismentioning
confidence: 99%